Articulating biological and social approaches in child and adolescent psychiatry - Guessoum, Sélim Benjamin; Benoit, Laelia; Thomas, Isaiah; Mallet, Jasmina; Sibeoni, Jordan; Hanin, Cyril; Moro, Marie Rose (Frontiers in Child and Adolescent Psychiatry, 2022)
Child and adolescent psychiatry has been based on numerous fields of research and theories, including neuroscience, physiology, psychology (developmental, psychodynamic, systemic, cognitive-behavioral, etc.), anthropology, sociology, and education sciences. Integrating transdisciplinary knowledge in multi-level models is an ongoing challenge for the future that is not immediately applicable in clinical practice and research. Articulating, i.e., to connect, to be jointed, (psycho)biological and (psycho)social approaches in child and adolescent psychiatry is a daily challenge for clinicians and researchers. Research is often limited to specific fields whereas real-life clinical practice needs a pluralistic approach. Research designs, tools, and clinical training need to provide knowledge applicable to the necessarily pluralistic daily clinical practice. This article provides some perspectives on how to articulate biological and social approaches, from research to clinical practice, and discusses the concept of pluralistic approaches, multimodal interventions, and how to provide articulated mental health care and training. Suggestions to better articulate biological and social approaches are provided: (I) State that the research object can be approached from different theoretical, research and clinical angles and explain the one chosen; (II) Propose synthesis articles that articulate biological and social knowledge; (III) Design biological studies that take into account social factors, and design social studies that take into account biological factors; (IV) Design transcultural tools; (V) Build pluralistic interventions, i.e., therapeutic modalities and mental health care settings that articulate biological and social approaches; (VII) Develop training in pluralistic articulated care.